Digital competency of Psychologists in Aotearoa New Zealand: A cross-sectional survey - Dobson, Rosie; Variava, Rushaina; Douglas, Meihana; Reynolds, Lisa M. (Frontiers in Digital Health, 2022)
Background: The increasing implementation of digital health into psychological practice is transforming mental health services. Limited clinical resources and the high demand for psychological assessments and interventions, alongside the restrictions imposed on services during the global COVID-19 pandemic, have been a catalyst for significant changes in the way psychologists work. Aim: This study aimed to explore the digital competence of psychologists working in Aotearoa New Zealand and their use of digital tools in the practice. Methods: A descriptive cross-sectional online survey was conducted with New Zealand Registered Psychologists (n=195) between July and November 2021. Results: Participants reported varying degrees of competence across the digital tasks presented with participants most commonly reporting moderate to high competence for engaging in remote supervision via digital means (86%) and obtaining client's informed consent for digital work (82%). In contrast, tasks that participants most commonly reported not being moderately or highly competent in included working with interpreters remotely (86%) and evaluating the effectiveness and security of smartphone apps (79%). Motivations to use digital technologies included meeting client preferences and needs, necessity for continuity of care, and the benefits of increased accessibility and reach. In contrast, the barriers to using digital technologies included client characteristics or preference, clinical factors, clinician preferences and skills, and workplace and technical issues or concerns. The majority (91.1%) were potentially interested in further training in this area. Conclusions: The current work offers insights into the digital competencies of a workforce that has required rapid incorporation of technologies into professional practice over recent years. This snapshot study into the digital skills of psychologists demonstrates a large variation in digital competence. In the current context, developing digital competencies seems a fundamental requirement for psychologists to work in ways that appropriately deliver client-centred care.